The effects of proving background knowledge in English lessons on college students’ reading comprehension ability : - Lê, Ngọc Vân Thủy (Đại học Cần Thơ, 2011)
This study attempts in teaching reading as well as to see whether students’ reading comprehension ability can develop through teachers’ providing background knowledge in reading lessons in the course-book